2021
DOI: 10.5093/apj2021a23
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making Styles in Adolescent Offenders and Non-offenders: Effects of Emotional Intelligence and Empathy

Abstract: The literature indicates that adolescents with delinquent behavior have greater difficulty making rational decisions and show lower emotional intelligence and empathy. Decision-making is a set of complex processes associated with neurobiological, cognitive, emotional, and social factors which help regulate and guide behavior, which could be influenced by emotional intelligence and empathy. A comparative, correlational, and predictive study was conducted to analyze relationships and influence of emotional intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
(103 reference statements)
1
5
0
2
Order By: Relevance
“…The first-order structure with four correlated dimensions was confirmed, and all subscales showed acceptable internal consistency (α ranged between 0.82 to 0.88). These results align with the model proposed by the authors (Mann et al, 1997) and corroborated in various studies that adapted the mdmq (Alzate-Saez de Heredia et al, 2004;Bailly & Ilharragorry-Devaux, 2011;Bouckenooghe et al, 2007;Cardona-Isaza et al, 2021;Colakkadioglu & Deniz, 2015;Cotrena et al, 2018;Filipe et al, 2020;Mann et al, 1997;Sarmany-Schuller, 1999;Tipandjan, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The first-order structure with four correlated dimensions was confirmed, and all subscales showed acceptable internal consistency (α ranged between 0.82 to 0.88). These results align with the model proposed by the authors (Mann et al, 1997) and corroborated in various studies that adapted the mdmq (Alzate-Saez de Heredia et al, 2004;Bailly & Ilharragorry-Devaux, 2011;Bouckenooghe et al, 2007;Cardona-Isaza et al, 2021;Colakkadioglu & Deniz, 2015;Cotrena et al, 2018;Filipe et al, 2020;Mann et al, 1997;Sarmany-Schuller, 1999;Tipandjan, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, vigilance and hypervigilance subscales had a small and positive association. This was an unexpected result since, in most studies, positive associations have only been found between non-vigilant decision-making styles, while a negative or no association at all has been reported pertaining to vigilant style and the non-vigilant dimensions (Alzate-Saez de Heredia et al, 2004;Cardona-Isaza et al, 2021;Colakkadioglu & Deniz, 2015;Cotrena et al, 2018;Filipe et al, 2020;Mann et al, 1997). This last finding could suggest that even when individuals display a more rational and organized decisional pattern behavior, they might also experience time pressure and stress generated by the decisional conflict, therefore, shifting to a hypervigilant decisional style to reach an adequate solution without the elaborated and exhaustive analytic procedures.…”
Section: Discussionmentioning
confidence: 93%
“…TE's influence on cognition has been extensively studied [46][47][48][49][50]. For instance, using a dot-probe paradigm and eye-tracking technique to investigate attention bias toward happy faces and positive words in participants with high and low empathy, Liu et al [48] found that trait empathy influenced the processing of emotional information.…”
Section: The Influence Of Trait Empathy On the Believability Of Newsmentioning
confidence: 99%
“…The influence of TE on cognition has been extensively studied [24][25][26][27][28]. For instance, using a dot-probe paradigm and eye-tracking technique to investigate the attention bias towards happy faces and positive words in participants with high and low empathy, Liu et al [55] found that trait empathy influenced the processing of emotional information.…”
Section: The Influence Of Trait Empathy On the Believability Of Newsmentioning
confidence: 99%